The Influence of Leadership and Motivation on Employee Performance at Dinas Pendidikan of Batam City - Indra Firdiyansyah (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2018)
This research in did is to find out if there’s the influence of leadership of the performance of employes in the batam city to find out if there’s the influence of motivation against the performance of the official education in batam city to know wheter there is the influence of leadership and motivation together about performance of employer for official education. In this study author using sample as much as 55 people employes taken in proportional to the sample census method. While the kind of used data is the primary data and data secondary the primary data from the kuisioner with of employees who are competent and official batam city education. The source of data in gain from document education in batam service. The techniques collecting data do statistic with interview and kuisioner. Data analitic to do with descriotive statistic, which serves for using to descriptive for give the picture/ilustration to the object in conscientious through samples data or population in got in the field connected with theories nrelevant as well as quantitative that’s analitic for the data that has been given score in accordance with scale of measurement to used the likert scale. From on the results of research. Than can to know about leadership and motivation for emlpoyees performance to official education Batam city overall as much as 72,1%. Keywords: Leadership, Motivation, Performance